2022
DOI: 10.3390/insects13060515
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Thiamethoxam and Deformed Wing Virus Type A on Wing Characteristics and Expression of Immune and Apoptosis Genes in Apis mellifera

Abstract: Honey bees are economically important insects for crop pollination. They play a significant role as pollinators of wild plants and agricultural crops and produce economical products, such as honey, royal jelly, wax, pollen, propolis, and venom. Despite their ecological and economical importance, the global honey bee population is in decline due to factors including pathogens, parasites, intensive agriculture, and pesticides. Moreover, these factors may be interlinked and exacerbate the loss of honey bees. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…In the bumblebee Bombus terrestris , the level of hymenoptaecin gene expression increased after injection of IAPV [ 204 ]. Similarly, A. mellifera infection with DWV as well as concomitant exposure to DWV type A and a pesticide thiamethoxam resulted in increased expression of the hymenoptaecin gene [ 205 , 206 ]. Mookhploy et al showed that the level of hymenoptaecin and defensin expression increased after injection of DWV into A. mellifera pupae, while abaecin and hymenoptaecin genes were upregulated in newly emerged adult bees [ 207 ].…”
Section: Amps In Antiviral Responsementioning
confidence: 99%
“…In the bumblebee Bombus terrestris , the level of hymenoptaecin gene expression increased after injection of IAPV [ 204 ]. Similarly, A. mellifera infection with DWV as well as concomitant exposure to DWV type A and a pesticide thiamethoxam resulted in increased expression of the hymenoptaecin gene [ 205 , 206 ]. Mookhploy et al showed that the level of hymenoptaecin and defensin expression increased after injection of DWV into A. mellifera pupae, while abaecin and hymenoptaecin genes were upregulated in newly emerged adult bees [ 207 ].…”
Section: Amps In Antiviral Responsementioning
confidence: 99%